Use of response surface methodology (RSM) for the identification of the best extraction conditions for headspace solid-phase micro extraction (HS-SPME) of the volatile profile of cv. Arbequina extra-virgin olive oil - Borges, Thays H. (2018)
The effect of the experimental conditions on assessing the global volatile profile of extra virgin olive oils (EVOO) by headspace solid-phase microextraction/gas chromatography-mass spectrometry (HS-SPME/GC–MS) is studied to obtain maximization of the total peak areas of the compounds. Response Surface Methodology (RSM) is applied to Arbequina EVOO, and the influence of oil quantity, extraction time, and extraction temperature on the total area and extraction of the major desirable compounds is analyzed. The experimental data are adequately fitted into second-order polynomial models with non-significant lack of fit (p>0.05) and coefficients of determination (R2 and R2-adjusted) higher than 0.88 and 0.78, respectively. A strong similarity is found between the predicted and experimental values. Furthermore, the surface plots show that the extraction of the volatile compounds is favored with increasing extraction temperature, time, and oil quantity. The extraction conditions to obtain the maximum response of “green” volatile compounds from Arbequina olive oil by HS-SPME placed in 50 mL vials are 4.6 g of oil, 43 min, and 59 ºC. Practical Applications: The findings of the present work show that specific conditions of HS-SPME/GC–MS affect the extraction of volatile compounds from cv. Arbequina olive oil and establish the optimum extraction parameters to more efficiently determine the global profile of this fraction, taking into account the organoleptic characteristics of the cultivar. The results also contribute to the knowledge of the volatile profile of the monovarietal olive oil cv. Arbequina, which is one of most cultivated and consumed types of olive oil worldwide.